A comparative analysis of locally sourced feeding systems on chicken body weight gain in Malaysia - Wong, Yuen Hwa (2024)
The surge in global poultry popularity has led to increased chicken meat consumption. The pandemic-induced rise in imported chicken feed prices has adversely affected the profitability of the chicken meat business. This situation prompted an investigation into the impact of four locally sourced feeding systems on chicken body weight gain, aiming to enhance the profitability of Malaysia’s chicken meat industry. The study, conducted on a Malaysian farm with 200 chickens, analyzed Feeding 1 (Premier Starter Feed (PSF) - Control Feed), Feeding 2 (PSF + SK Gold yellow powder), Feeding 3 (PSF + crude palm kernel oil) and Feeding 4 (PSF + PERFAT Pfi-7 organic acid). Over 14 weeks and 2,800 observations, Engle & Granger’s Vector Autoregression estimation procedure was employed, revealing a positive correlation between chicken age and feeding systems impacting chicken body weight. Feeding 3, incorporating crude palm kernel oil, exhibited the most significant influence on chicken body weight gain, emerging as the optimal and effective choice for improving the chicken meat business. The model’s reliability was affirmed by consistent experimental results, rendering the findings applicable to the commercial market. In conclusion, this research establishes that Feeding 3 is the most efficient, offering valuable insights for commercial applications.